2013
DOI: 10.1186/1471-2164-14-657
|View full text |Cite
|
Sign up to set email alerts
|

Targets of light signalling in Trichoderma reesei

Abstract: BackgroundThe tropical ascomycete Trichoderma reesei (Hypocrea jecorina) represents one of the most efficient plant cell wall degraders. Regulation of the enzymes required for this process is affected by nutritional signals as well as other environmental signals including light.ResultsOur transcriptome analysis of strains lacking the photoreceptors BLR1 and BLR2 as well as ENV1 revealed a considerable increase in the number of genes showing significantly different transcript levels in light and darkness compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
161
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(173 citation statements)
references
References 62 publications
10
161
0
2
Order By: Relevance
“…Recent studies of a Neurospora crassa Vivid (VVD) homologue from T. reesei (ENV1) revealed divergent signaling mechanisms within closely related fungal LOV domains (11,32,33). Initial photochemical characterization confirmed LOV type chemistry, with a time constant for adduct scission of ϳ1,500 s (11).…”
Section: Resultsmentioning
confidence: 92%
“…Recent studies of a Neurospora crassa Vivid (VVD) homologue from T. reesei (ENV1) revealed divergent signaling mechanisms within closely related fungal LOV domains (11,32,33). Initial photochemical characterization confirmed LOV type chemistry, with a time constant for adduct scission of ϳ1,500 s (11).…”
Section: Resultsmentioning
confidence: 92%
“…This suggests that these genes can be expected to be potentially regulated in response to light and to a nutrient signal as transmitted via the heterotrimeric G-protein pathway. Members of all GH families detected in T. reesei were found to be potentially subject to light regulation, and many of them are regulated by the photoreceptors BLR1, BLR2, or ENV1 (351).…”
Section: Cazymesmentioning
confidence: 99%
“…Gyalai-Korpos et al [98] considered that the effect on cellulase activity of blr1 and blr2 deletion was due to differences in protein secretion and that of env1 deletion due to adjustments in response to the environment. Tisch and Schmoll [27] described a key difference in the functioning of the homologous proteins in T. reesei and N. crassa. Transcriptional analysis of deletion mutants under light and dark conditions showed that photoreceptor regulation of carbon metabolism is mediated by BLR1 and BLR2 stimulation of env1 transcription in T. reesei, whereas in N. crassa VIVID had a negative effect on the WCC [27].…”
Section: Light Regulation Of Cazyme-encoding Gene Expressionmentioning
confidence: 99%
“…Tisch and Schmoll [27] described a key difference in the functioning of the homologous proteins in T. reesei and N. crassa. Transcriptional analysis of deletion mutants under light and dark conditions showed that photoreceptor regulation of carbon metabolism is mediated by BLR1 and BLR2 stimulation of env1 transcription in T. reesei, whereas in N. crassa VIVID had a negative effect on the WCC [27]. Also, BLR1 and BLR2 in T. reesei are not considered to act as a complex under darkness [98].…”
Section: Light Regulation Of Cazyme-encoding Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation